Evaluation of the Diagnostic Value of Cell Population Data in Sepsis in Comparison to Localized Infection, Chronic Inflammation, and Noninfectious Inflammation Cases. - DİRESKENELİ, RAFİ HANER; KAYA, ÖZLEM; GÜL, FETHİ; İNANÇ, GÜZİDE NEVSUN; İLKİ, ZEYNEP ARZU; ŞİRİKÇİ, ÖNDER; HAKLAR, GONCAGÜL (My University, 2022)
Introduction Sepsis, defined as an increase of 2 points or more in the sequential organ failure assessment score, is a life-threatening organ dysfunction caused by the dysregulated host response to infection. Volume-conductivity-scatter (VCS) parameters of cell counters which are known as cell population data (CPD) have been suggested to be beneficial in diagnosing sepsis. We aimed to evaluate the diagnostic value of CPD parameters in sepsis in comparison to nonsystemic infection cases (NSI) and non-infectious acute and chronic inflammatory conditions. Materials and Methods We prospectively included four groups of patients” data: sepsis (n = 66), localized infection (pneumonia, n = 59), chronic inflammation (rheumatoid arthritis, n = 92) and noninfectious inflammation (coronary artery bypass graft operation, n = 56) groups, according to their clinical status and laboratory results. Samples for cell counting and serum markers were collected on the same day of culture collection. VCS parameters were measured by Unicel DxH800 Coulter Cellular Analyzer (Beckman Coulter, USA). Results Mean neutrophil volume (MN-V-NE), was highest in the sepsis group [155(149-168)] compared to the localized infection [148(140-158)], chronic inflammation [144.5(142-149)] and noninfectious inflammation [149(145.2-153.7)] (P = 0.001, P < 0.001, P < 0.001, respectively). Neutrophil volume SD (SD-V-NE) was higher in the sepsis [21(18.8-23.7)], significantly differentiating sepsis from other groups. The area under curves of procalcitonin and hs-C-reactive protein were 0.846 and 0.837, respectively, in the receiver-operating characteristic curves (ROC) . CPD combinations, (SD-V NE + SD-V LY + SD-V MO), (SD-V NE + SD-V MO), and (MN-V NE + SD-V NE + SD-C LY + SD-V MO) had greater AUC values than procalcitonin’s. Conclusion VCS parameters might be promising for differentiating sepsis and non-sepsis cases. Additionally, obtaining these data routinely makes their prospects promising without any additional cost and time.